Unconventional, partisan, and polarizing rhetoric : how the 2016 election shaped the way candidates strategize, engage, and communicate - Kraybill, Jeanine E. (Voting, elections, and the political process., 2017)
"This work examines how political rhetoric and communication shaped the contours, characteristics, and outcomes of the 2016 presidential election. The contributors demonstrate that voters were primed for an outsider candidate and how various rhetorical and communication strategies ultimately influenced the outcome of the election."--Provided by publisher